Bosnia and Herzegovina : 2012 Article IV Consultation and Request for Stand-By Arrangement-Staff Report; Informational Annex; Public Information Notice; Press Release; and Statement by the Executive Director for Bosnia and Herzegovina. (IMF Staff Country Reports; Country Report ;, 2012)
Bosnia and Herzegovina's (BiH) challenge is to cope with the adverse economic environment and prepare the ground for achieving sustainable export-led economic growth, raising living standards, and making progress toward EU accession. In addition to fiscal consolidation, this will require reforms to improve the composition of public expenditure and unlock the economy's potential. Financial sector policies should aim at further enhancing the authorities' crisis preparedness and contingency planning. These policies would also provide a solid basis for the stability of the currency board and enhanced national policy coordination.